STUDENTS AND STUDYING YOUTH IN THE REVOLUTION OF 1905-1907 - Boris K. Tebiev (Высшее образование в России)
On the basis of archival materials and literature sources the article addresses the participation of students in the events of the First Russian revolution of 1905-1907. The study focuses on the problems of formation and development of students' and pupils' self-government, the essence of the demands of the youth in the area of public and academic arrangement, democratization of the education system. Owing to the experience in the sphere of political socialization, the Russian students could comprehend the essence of the monarchical system of Russia, evaluate the educational doctrine of the autocracy and the practical measures of the state in the sphere of public education and come to the idea of creation of a new school based on the principles of democracy and humanism.